Meta Analysis: Application of Health Belief Model Theory on Pap Smear Screening Uptake in Women of Reproductive Age - Syndia Puspitasari; Bhisma Murti; Hanung Prasetya (Journal of Health Promotion and Behavior, 2022)
Background: Cervical cancer is the fourth cancer in the world that attacks women and causes death. Until now, cervical cancer causes high morbidity and mortality. Regular cervical cancer screening with the Papanicolaou (Pap) smear test remains an effective public health intervention in the prevention and subsequent reduction of the incidence, morbidity and mortality of cervical cancer. Health Belief Model (HBM) is a model developed to help understand human behavior in seeking health services and explain why people do not engage in behavior for disease prevention or early detection.Subjects and Method: This was a systematic review and meta-analysis. Data collection was obtained from 3 databases, namely: Google Scholar, PubMed, and Science Direct. Analysis of this research using software RevMan 5.3. The inclusion criteria used were full English paper with cross sectional design in 2012-2022. The keywords used were “Pap Smear” OR “Cervical Cancer Screening” AND “Health Belief Model” OR “Health Belief” AND “Cervical Cancer”.Results: A total of 15 cross-sectional study articles from Indonesia, Malaysia, Turkey, Nepal, Lebanon, South Korea, Iran, South Africa, Ethiopia, the United States, and Italy were reviewed in the meta-analysis. Based on the results of the analysis, it was found that the perception of high susceptibility had an effect on the possibility of using Pap smear services 1.13 times compared to the perception of low susceptibility (aOR= 1.13; 95% CI= 1.03 to 1.07; p < 0.001), and the results were statistically significant. The perception of low barriers affects the possibility of using Pap smear services 0.91 times compared to perceptions of high barriers (aOR = 0.91; 95% CI = 0.86 to 0.97; p <0.001), and the results are statistically significant.Conclusion: Perceptions of high susceptibility and perceptions of low barriers affect the possibility of using pap smear services.Keywords: health belief model, cervical cancer, pap smear.Correspondence:Syndia Puspitasari. Masters Program in Public Health, Universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: syndiapuss96@gmail.com. Mobile: +628 2234398706.Journal of Health Promotion and Behavior (2022), 07(04): 322-335DOI: https://doi.org/10.26911/thejhpb.2022.07.04.05